2019
DOI: 10.3390/ijms20020341
|View full text |Cite
|
Sign up to set email alerts
|

Development of Natural Product-Conjugated Metal Complexes as Cancer Therapies

Abstract: Platinum-based drugs have revolutionized cancer care, but are unfortunately associated with various adverse effects. Meanwhile, natural product scaffolds exhibit multifarious bioactivities and serve as an attractive resource for cancer therapy development. Thus, the conjugation of natural product scaffolds to metal complexes becomes an attractive strategy to reduce the severe side effects arising from the use of metal bearing drugs. This review aims to highlight the recent examples of natural product-conjugate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 80 publications
(86 reference statements)
0
18
0
1
Order By: Relevance
“…CoMeDs combines two different agents, such as silver(I) with penicillin to create new agents with new properties from the superimposition of those initially possessed by the constituents [6][7][8][9][10][11][12]. Although the term "conjugate" is more properly used for polymer-drugs or dendrimer-drug conjugates where nanoparticles are formed, recently, the term CoMeD has also been used to emphasize the synergistic effect of the coordination of a metal with drugs [13,14]. Furthermore, the solvent type affects the structure of the metal-drug complexes, leading to the formation of polymeric structures by the metal-drug-solvent conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…CoMeDs combines two different agents, such as silver(I) with penicillin to create new agents with new properties from the superimposition of those initially possessed by the constituents [6][7][8][9][10][11][12]. Although the term "conjugate" is more properly used for polymer-drugs or dendrimer-drug conjugates where nanoparticles are formed, recently, the term CoMeD has also been used to emphasize the synergistic effect of the coordination of a metal with drugs [13,14]. Furthermore, the solvent type affects the structure of the metal-drug complexes, leading to the formation of polymeric structures by the metal-drug-solvent conjugation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the development of agents with enhanced anticancer properties via the coordination of biologically active molecules to metals, more specifically ruthenium, has attracted increasing attention [36][37][38]. Because ruthenium complexes are widely studied for their ability to induce cancer cell death, the introduction of biologically active ligands in their structure can be a promising approach for the development of drug candidates with a broader range of anticancer activities compared to ruthenium complexes or ligands alone [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…The precursor cobalt­(III) complexes [Co­(B) 2 Cl 2 ]Cl (B = phen, dpq, and dppz) were prepared by oxidizing the corresponding cobalt­(II) complexes using dry chlorine gas . Dry chlorine gas was prepared in situ by reacting KMnO 4 with concentrated hydrochloric acid and passing the resulting gas through concentrated sulfuric acid …”
Section: Methodsmentioning
confidence: 99%
“…Natural products have gained popularity as emerging sources for developing anticancer drugs, and the role of natural products in designing PDT drugs has recently been highlighted. , Esculetin (6,7-dihydroxycoumarin) is a naturally occurring coumarin derivative found in plants and is known to possess significant anticancer activity against various cancers . Studies have shown that esculetin can act as a photosensitizer for DNA damage .…”
Section: Introductionmentioning
confidence: 99%